2017
DOI: 10.1088/1361-6528/aa7769
|View full text |Cite
|
Sign up to set email alerts
|

Structural and photoluminescence properties of silicon nanowires extracted by means of a centrifugation process from plasma torch synthesized silicon nanopowder

Abstract: We report on a method for the extraction of silicon nanowires (SiNWs) from the by-product of a plasma torch based spheroidization process of silicon. This by-product is a nanopowder which consists of a mixture of SiNWs and silicon particles. By optimizing a centrifugation based process, we were able to extract substantial amounts of highly pure Si nanomaterials (mainly SiNWs and Si nanospheres (SiNSs)). While the purified SiNWs were found to have typical outer diameters in the 10-15 nm range and lengths of up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…In particular, QC-induced PL emission has been reported to occur at 1.93 eV (640 nm) for 5 nm-diameter SiNW and to redshift with increasing diameters [ 13 ], exhibiting a few tens of μs recombination time [ 14 ]. In the recent past, we measured the PL spectra on SiNC and SiNW with diameter down to 2–3 nm, confirming the presence of PL features located between 600 and 950 nm (2.0–1.3 eV) [ 15 ]. More recently, we showed that amorphous silicon oxide presents PL in such a spectral range due to band-tail recombination [ 16 ].…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…In particular, QC-induced PL emission has been reported to occur at 1.93 eV (640 nm) for 5 nm-diameter SiNW and to redshift with increasing diameters [ 13 ], exhibiting a few tens of μs recombination time [ 14 ]. In the recent past, we measured the PL spectra on SiNC and SiNW with diameter down to 2–3 nm, confirming the presence of PL features located between 600 and 950 nm (2.0–1.3 eV) [ 15 ]. More recently, we showed that amorphous silicon oxide presents PL in such a spectral range due to band-tail recombination [ 16 ].…”
Section: Introductionsupporting
confidence: 57%
“…From the process described in refs. [ 15 ] and [ 28 ], we obtained a condensate consisting of a blend of NW (with diameters in the few nm range and up to several microns long) and silicon spheres with diameters ranging from 10 s of nm to few µm. Aimed by the purpose of selecting the NW population from the silicon spheres, the as-grown (AG) Si nanopowder was dispersed in isopropanol (IPA, Merck KGaA, Darmstadt, Germany) at a concentration of 0.5 mg/mL and ultrasonicated for 5 min in a 200 W ultrasonic bath.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of new Si-based nanohybrids was demonstrated via high-temperature thermal annealing of ultrathin core/shell Si/SiO 2 nanowires synthesized via an ICP-based process [5,34,35]. The formation mechanisms of these Si hybrid nanostructures was described on the basis of instability phenomena undergone by the inner Si core of the ICP-SiNWs when subjected to high-temperature annealing conditions.…”
Section: Resultsmentioning
confidence: 99%